A Practical Review of Insulin Pen Devices - Teresa L. Pearson (European Medical Journal Diabetes, 2014)
Since the advent of insulin pens in 1985, there have been ongoing improvements providing several advantages over the traditional vial and syringe method of insulin delivery. In recent years, pens have become increasingly user-friendly, and some models are highly intuitive to use, requiring little or no instruction. Despite this progress, there remains to be disparity in access to insulin pens to people with diabetes in various countries. There is a need for improved awareness of the benefits of insulin pens among healthcare professionals. Continual advances have been made to address patient needs such as improved technology to make them easier to use; less painful; more discreet and convenient; and more accuracy for small doses of insulin, as well as the incorporation of a memory function, all contribute to an insulin delivery device that allows the patient to better manage their diabetes anytime and anyplace, without the bulk and challenge of carrying a vial and syringe. These advances have resulted in increased patient satisfaction with insulin pens and most importantly, all of these benefits improve adherence and result in improved clinical outcomes. This review highlights these benefits of insulin pen use and presents the issues to be considered when helping patients decide on the insulin pen that will best suit their needs.